Familial Mediterranean Fever: Observations from a pilot gene expression microarray analysis study - Mahfouz, R.; Kreidieh, K.; Khalek, R. A.; Yazbek, S. (Cellular and Molecular Biology, 2017)
Familial Mediterranean Fever (FMF) is an autosomal recessive autoinflammatory disease affecting people of Mediterranean ancestry. The disease is caused by mutations in the MEFV gene located on chromosome 16p13.3. The aim of this pilot study was to assess global gene expression and identify genes and pathways involved in FMF that could be downstream to MEFV mutations or could be novel involved. EDTA blood samples were collected from 14 patients showing FMF-like symptoms and age-matched to 7 controls showing healthy conditions. Microarray was used to assess global gene expression and identify genes and pathways involved in FMF. When we compared individuals with MEFV mutations (homozygous and heterozygous) to control group, probe sets of receptor proteins HLA-DQA1 and HLA-DQB1 were significantly over expressed by 5 folds among the patients group. Despite its limitations, this pilot study could strongly suggest that the role of HLA be investigated in the pathogenesis of MEFV mutation and as a potential moderator explaining penetrance and variation in symptoms among patient groups.